The Relationship of Behavioral Factors with Investment Performance of Individual Investors in the Nepali Stock Market (Prithvi Academic Journal, 2021)
In recent years, the market anomalies and irrational behavior of investors have influenced the stock market worldwide. The impact of investor behavior on the stock market is more prominent in small and less efficient capital markets. The study is based on the questionnaire survey of 203 investors from Kathmandu and Pokhara. The study uses Exploratory Factor Analysis (EFA) to explore the underlying dimensions of investor behavior employing Principal Component Analysis and Varimax rotation. The suitability of the data for the factor analysis has been examined using KMO and Barlett’s Test of Sphericity. The EFA extracted four factors of investor behavioral dimensions categorized as: heuristics, prospects, market factors and herding effect. The factor scores obtained from the EFA was used to examine the correlation of these behavioral factors with investment performance. The results reveal that behavioral biases like heuristics, prospects, market factor and herding effect are present among individual investors in Nepal. Among the factors, the investment performance of investors is found to be influenced by heuristics and market factors. The heuristic behaviors are found to have the highest and positive influence on the investment performance. Finally, the results depict that following the herd behavior in the market and prospects does not result in the improved investor performance. The findings are helpful to understand the role of investor behavior in the stock market and formulation of appropriate policies that limit the possibility of behavioral biases affecting the stock market adversely.